Tidal Effect on Recruitment East Larvae Fish In East Pelawangan Segara Anakan Cilacap - Subiyanto Subiyanto; Niniek Widyorini; Iswahyuni Iswahyuni (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2009)
Observations on transport of fish larvae during low tide in the East Sea has been done Pelawangan interest from July to September 2003. Sampling is performed using Plankton nets 60 cm in diameter and 200 mesh size, as many as 5 times in the full month, either at the time of high tide or low tide. Net withdrawals are carried out for 10 minutes at 2 knots. During studies have arrested 904 individual which consist of 11 families, there are Clupeidae, Engraulididae, Belonidae, Hemiramphidae, Atherinidae, Mugillidae, Ambassidae, Apogonidae, Gerreidae, Pomacentridae, Gobiidae. Most fish larvae are caught fish larvae, adult stage in the sea. Observations show that the influence of tidal changes of fish larvae in the East Pelawangan. Where the tide arrested 472 people (52.21%) and at low tide arrested 432 people (47.79%).  Key words : Tidal, Recruitment, Fish larvae